Psychiatric treatment with people displaced in or from fragile states - Buckley, V (Refugee Studies Centre, University of Oxford, 2013)
A fragile state is not an ideal environment for any professional to work within – psychiatric, medical or otherwise. Psychiatrists working to assess psychological distress and mental health in fragile states, or with refugees from fragile states, need to adopt flexible approaches.